THE CONTRIBUTION OF INCOME FROM FEMALE WORKERS IN THE INFORMAL SECTOR TO HOUSEHOLD EXPENDITURE IN SOUTH KUTA DISTRICT - Ni Luh Putu Linda Kusuma Dewi; Ida Ayu Nyoman Saskara (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study focuses on quantifying the income provided by female workers in the informal sector for household expenditure, with a case study in South Kuta District. The data used in this study are primary data collected from 97 respondents selected as the research sample. The sampling method employs a non-probability sampling technique, specifically purposive sampling. The study applied descriptive statistics and multiple linear regression to analyze the data. The results of the study indicate that the variables of women’s income in the informal sector, the number of family dependents, the husband’s income, and the allocation of time for mothers to work simultaneously exert a positive and statistically significant influence on household expenditure. The contribution of income from female workers in the informal sector to household expenditure reached 83,59 percent, indicating that the income of women plays a crucial role in supporting the family economy.